Hepatopancreas-Specific Lectin Participates in the Antibacterial Immune Response by Regulating the Expression of Antibacterial Proteins - Cao, Xiao-Tong; Pan, Xiao-Yi; Sun, Meng; Liu, Yan; Lan, Jiang-Feng (Frontiers in Immunology, 2021)
The hepatopancreas is an important digestive and immune organ in crustacean. There were low but stable numbers of microbes living in the hemolymph of crustacean, whereas the organs (including hepatopancreas) of crustacean were immersed in the hemolymph. It is very important to study the immune mechanism of the hepatopancreas against bacteria. In this study, a novel CTL (HepCL) with two CRDs, which was mainly expressed in the hepatopancreas, was identified in red swamp crayfish (Procambarus clarkii). HepCL binds to bacteria in vitro and could enhance bacterial clearance in vivo. Compared with the C-terminal CRD of HepCL (HepCL-C), the N-terminal CRD (HepCL-N) showed weaker bacterial binding ability in vitro and stronger bacterial clearance activity in vivo. The expression of some antimicrobial proteins, such as FLP, ALF1 and ALF5, was downregulated under knockdown of HepCL or blocked with Anti-HepCL after challenge with Vibrio in crayfish. These results demonstrated that HepCL might be involved in the antibacterial immune response by regulating the expression of antimicrobial proteins.